2019
DOI: 10.1021/acsphotonics.8b01576
|View full text |Cite
|
Sign up to set email alerts
|

PSF Distortion in Dye–Plasmonic Nanomaterial Interactions: Friend or Foe?

Abstract: Plasmonic nanostructures offer promising applications as nanocatalysts, but optimizing their structure−function relationship using optical superlocalization techniques is hindered by the formation of distorted point spread functions (PSFs). Previously reported localization bias for remotely excited Alexa-647 adsorbed to Ag nanowires is investigated here for its potential to provide useful information about surface interactions. Two main classes of abnormal PSFs are examined: single-lobed PSFs, in which the loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 72 publications
1
34
1
Order By: Relevance
“…Furthermore, by fixing the orientation of the emitter, not only the effect of emitter location but also orientation could be studied to reveal polarization-dependent properties that are usually lost due to orientation averaging. Ideally, multimodal imaging may enable the collection of emission intensity, PSF shape, 17 fluorescence lifetime, 29 emission polarization, 42 and single-molecule spectra 43 to obtain a complete picture of particle–emitter coupling. Such experiments will shed light on the effect of a 3D photonic environment on optical imaging and will extend the realm of super-resolution microscopy to nano- and micrometer-sized colloids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, by fixing the orientation of the emitter, not only the effect of emitter location but also orientation could be studied to reveal polarization-dependent properties that are usually lost due to orientation averaging. Ideally, multimodal imaging may enable the collection of emission intensity, PSF shape, 17 fluorescence lifetime, 29 emission polarization, 42 and single-molecule spectra 43 to obtain a complete picture of particle–emitter coupling. Such experiments will shed light on the effect of a 3D photonic environment on optical imaging and will extend the realm of super-resolution microscopy to nano- and micrometer-sized colloids.…”
Section: Resultsmentioning
confidence: 99%
“… 19 In some studies mislocalization was observed as a dominant effect, 16 , 18 22 other studies reported it to be negligible compared to the localization precision of the microscope, 4 , 35 and some studies reported exotic multilobed PSFs. 15 , 17 The variation in reported effects has its root largely in the different particle size, shape, and material used as well as the particle–emitter spacing and spectral detuning.…”
Section: Introductionmentioning
confidence: 99%
“…[136]. (b) Baiyasi et al [139] provide clear observation of the dramatic change of PSFs for emitters near a nanostructure. Instead of simple Gaussian-like PSFs this includes multi-lobed PSFs.…”
Section: Challenges For Single Emitter Nanophotonics Experimentsmentioning
confidence: 99%
“…Numerical simulations reproduced these measured systematic artifacts. The significant shape changes of the PSF near nanostructures were thoroughly studied in the specific case of a silver nanowire in [138] and subsequently used by Baiyasi et al [139] to associate the measured PSF to a specific orientation of the dipole moment. Figure 7b illustrates this effect.…”
Section: Challenges For Single Emitter Nanophotonics Experimentsmentioning
confidence: 99%
“…The second is that it could produce significant signal enhancement which leads to higher localization precision, and is hence preferred. Hence, whether in this context, working with plasmonic metal is necessary or not is yet to be determined (Baiyasi et al, 2019 ).…”
Section: Challenges and Emerging Directionsmentioning
confidence: 99%